Handbook of biosensors and biosensor kinetics - Sadana, Ajit, 1947-; Sadana, Neeti (New York : Elsevier, 2011)
Biosensors are essential to an ever-expanding range of applications, including healthcare; drug design; detection of biological, chemical, and toxic agents; environmental monitoring; biotechnology; aviation; physics; oceanography; and the protection of civilian and engineering infrastructures. This book, like the previous five books on biosensors by this author (and one by the co-author), addresses the neglected areas of analyte-receptor binding and dissociation kinetics occurring on biosensor surfaces. Topics are covered in a comprehensive fashion, with homogeneous presentation for the benefit of the reader. The contributors address the economic aspects of biosensors and incorporate coverage of biosensor fabrication and nanobiosensors, among other topics. The comments, comparison, and discussion presented provides a better perspective of where the field of biosensors is heading. Serves as a comprehensive resource on biosensor analysis. Examines timely topics such as biosensor fabrication and nanobiosensors. Covers economic aspects and medical applications (e.g., the role of analytes in controlling diabetes).
1. Introduction -- 2. Modelling and Theory -- 3. Fabrication of Biosensors -- 4. Biosensors Involved in Drug Discovery -- 5. Nanobiosensors -- 6. Binding of the Same Analyte to Different Biosensor Surfaces -- 7. Binding of the Same Analyte (Glucose) to Different Biosensor Surfaces: A Fractal Analysis of the kinetics -- 8. Medical Applications of Biosensors -- 9. Physiological Cellular Reactions Detection on Biosensor Surfaces: A Fractal Analysis -- 10. Detection of Gases on Biosensor Surfaces -- 11. Detection of Analytes on Arrays/Microarrays/DNA Chips -- 12. Binding and Dissociation Kinetics of Different Analytes on Novel Biosensing Surfaces: A Fractal Analysis -- 13. Binding of Different Analytes on Biosensor Surfaces -- 14. Toxins and Pollutants Detection on Biosensor Surfaces -- 15. Fractal Analysis of the Binding and dissociation Kinetics of Protein Markers and other Medically Oriented Analytes on Biosensor Surfaces -- 16. Binding and Dissociation Kinetics During Hybridization on Biosensor Surfaces -- 17. Economics of Biosensors.
Includes bibliographical references and index.
Keywords: Biosensors; Dynamics